Treatment Challenges of a Primary Vertebral Artery Aneurysm Causing Recurrent Ischemic Strokes. (10th January 2017) - Strambo, Davide; Peruzzotti-Jametti, Luca; Semerano, Aurora; Fanelli, Giovanna; Simionato, Franco; Chiesa, Roberto; Rinaldi, Enrico; Martinelli, Vittorio; Comi, Giancarlo; Bacigaluppi, Marco; Sessa, Maria
Abstract : Background . Extracranial vertebral artery aneurysms are a rare cause of embolic stroke; surgical and endovascular therapy options are debated and long-term complication may occur. Case Report . A 53-year-old man affected by neurofibromatosis type 1 (NF1) came to our attention for recurrent vertebrobasilar embolic strokes, caused by a primary giant, partially thrombosed, fusiform aneurysm of the left extracranial vertebral artery. The aneurysm was treated by endovascular approach through deposition of Guglielmi Detachable Coils in the proximal segment of the left vertebral artery. Six years later the patient presented stroke recurrence. Cerebral angiography and Color Doppler Ultrasound well characterized the unique hemodynamic condition developed over the years responsible for the new embolic event: the aneurysm had been revascularized from its distal portion by reverse blood flow coming from the patent vertebrobasilar axis. A biphasic Doppler signal in the left vertebral artery revealed a peculiar behavior of the blood flow, alternately directed to the aneurysm and backwards to the basilar artery. Surgical ligation of the distal left vertebral artery and excision of the aneurysm were thus performed. Conclusion . This is the first described case of NF1-associated extracranial vertebral artery aneurysm presenting with recurrent embolic stroke. Complete exclusion of the aneurysm from the blood circulation is advisable to achieve full resolution of the embolic source.